War, violence and Rabindranath Tagore's quest for world peace - Quayum, Mohammad Abdul (Flinders University, Australia, 2017)
Rabindranath Tagore (1861-1941), India’s messianic poet and Asia’s first Nobel Laureate (1913), promulgated a vision of peace through the cultivation of the ideologies of Ahimsa, or non-violence, which he derived from the Bhagavad Gita and Advita, or one-identity of the universe, which he derived from the Upanishads. This paper investigates how Tagore formulated this vision of peace against a backdrop of and as an antidote to the reckless ‘jihadism’ (both religious and secular) and ‘war-madness’ of the twentieth century, which witnessed the two World Wars as well as an on-going violence in different forms, effectively turning the world into a ‘tower of skulls.’ He attributed this ‘devil dance of destruction’ to three intersecting forces: the unmediated materialism of modern society; belligerent nationalism which often led to nationalist selfishness, chauvinism and self-aggrandisement; and the machinery of organised religion which, he said, ‘obstructs the free flow of inner life of the people and waylays and exploits it for the augmentation of its own power.’ His response to it was the creation of a global human community, or a ‘grand harmony of all human races,’ by shunning exclusivism and dogmatism of all forms, and through the fostering of awareness that human beings were not only material and rational as creatures but also moral and spiritual, sharing a dew-drop of God in every soul.